Farm Business Feasibility of Pineapple Commodity after Volcanic Eruption in Ngancar District, Kediri, East Java Province - Risdiana Himmati; Yunastiti Purwaningsih; Agustinus Suryantoro (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2020)
This study aims to find and analyze the effect of the input factors of activities undertaken in farm businesses affected by a volcanic eruption on their farm business. This research concentrates on the feasibility of the planted commodity whether it can still be continued with the feasibility value based on the results of the R/C Ratio calculation or not. This study took place in a district located closest and suffered major damage due to the eruption of Mount Kelud in Ngancar District, Kediri Regency, East Java Province. This research used primary and secondary data. This study used the R/C Ratio method to analyze the feasibility of pineapple farm business in the Ngancar District, Kediri Regency. The results of the feasibility analysis of the pineapple farm business using the R/C Ratio show that the pineapple farm business is financially feasible after the eruption of Mount Kelud because it has an R/C ratio more than one.